A 90 - day repeated dose oral gavage toxicity evaluation study of the combined myo-inositol product s-femme in Wistar rats - Tung, Tran Thanh; Hien, Dang Thi Thu (Tạp chí Nghiên cứu Y học, 2026)
In the present study, a sub-chronic oral toxicity study was designed to assess the safety of S-FEMME powder in Wistar rats. The 90-day toxicity study was conducted by oral administration at doses of 0 (control), 0.12, and 0.36 sachets/kg/day for a continuous period of 90 days in Wistar rats. The evaluated parameters included body weight, clinical observations, hematological and biochemical analyses, gross necropsy, and histopathological assessment. The findings demonstrated that oral exposure to S-FEMME at both dose levels did not induce any clinical sign, no mortality, toxicologically significant changes in hematology, clinical biochemistry, macroscopic findings, or histopathological examination. In summary, the no-observed-adverse-effect-level (NOAEL) of S-FEMME is greater than 0.36 sachets/kg/day when administered orally for 90 consecutive days at two doses in Wistar rats.